Evaluating Socioeconomic Influences on English Language Proficiency among Secondary School Students in Trivandrum (Journal of Advances and Scholarly Researches in Allied Education, 2025)
English is becoming increasingly necessary for individuals to succeed in a globalized world. However, proficiency level varies due to various socioeconomic factors. This study examines the impact of socioeconomic factors on English language proficiency among secondary school students in Trivandrum, Kerala. Utilizing a quantitative and qualitative approach, the study examines a sample of 416 respondents, comprising of 32 principals, 64 school subject teachers (SST) and 320 students, which is selected through a random sampling technique. Structured questionnaires and interviews are used to collect data.  It is examined utilizing qualitative analysis including descriptive and inferential statistics. The study examines the significant influence of key variables such as gender, locality, socioeconomic status (SES), school type, duration of English learning, and academic performance on students' English language learning. The results show that there are significant differences in English language proficiency based on these variables, and also reveal that students from urban areas, higher socioeconomic backgrounds, and those with greater parental support and access to digital resources typically perform better in English.  Overall, the respondents of the study agreed that, SES has a substantial effect on learning English language at the secondary level.